CULTURAL LIFE IN CHIROQCHI PRINCIPALITY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the cultural life of Chiroqchi, a region located in the southwestern part of the Kashkadarya. The paper delves into the historical, literary, artistic, and educational aspects of Chiroqchi's culture, highlighting its rich heritage shaped by various civilizations and the significant role of the Jadid movement in modernizing education. The traditions, festivals, and family values in Chiroqchi are also discussed, emphasizing the importance of education and national identity. The article provides an overview of how the region's cultural life has developed over the centuries and continues to thrive today.